Antiarrhythmic medication classification based on pathogenetic cardiac arrhythmia mechanisms - T. N. Lipnitsky; V. A. Kozlovsky (Российский кардиологический журнал)
Antiarrhtytmic medication classification (AMC) was proposed by V. Williams and modified by D. Harrison in the time when antiarrhythmic activity of cardiac receptor and ion channel activators was less known, and their effects on bilipid sarcolemma layer was not regarded as a method for bioelectrical myocardial instability correction. The authors propose to divide all antiarrhythmic medications into four groups: ion channel function modulators, cardiac receptor modulators, ion pump function modulators, and membrane protectors. Each class is divided into sub-classes and groups.